Pomelo seed oil: Natural insecticide against cowpea aphid - Ling, Wei; Kaliaperumal, Kumaravel; Huang, Meiling; Liang, Yan; Ouyang, Zhigang; Zhou, Zhonggao; Jiang, Yueming; Zhang, Jun (Frontiers in Plant Science, 2022)
Cowpea aphid (Aphis craccivora Koch) is a plant pest that causes serious damage to vegetable crops. Extensive use of synthetic chemical pesticides causes deleterious effects on consumers as well as the environment. Hence, the search for environmentally friendly insecticides in the management of cowpea aphids is required. The present work aims to investigate the aphicidal activity of pomelo seed oil (PSO) on cowpea aphids, the possible insecticidal mechanisms, its chemical constituent profile, as well as the toxicity of its primary compounds. The results of the toxicity assay showed that PSO had significant insecticidal activity against aphids with a 72-hour LC50 value of 0.09 μg/aphid and 3.96 mg/mL in the contact and residual toxicity assay, respectively. The enzymatic activity of both glutathione S-transferase (GST) and acetyl cholinesterase (AChE) significantly decreased, as well as the total protein content, after PSO treatment, which suggested that the reduction of AChE, GST, and the total protein content in aphids treated with PSO might be responsible for the mortality of A. craccivora. The GC-MS analysis revealed that PSO contained limonene (22.86%), (9Z,12Z)-9,12-octadecadienoic acid (20.21%), n-hexadecanoic acid (15.79%), (2E,4E)-2,4-decadienal (12.40%), and (2E,4Z)-2,4-decadienal (7.77%) as its five major compounds. Furthermore, (9Z,12Z)-9,12-octadecadienoic acid showed higher toxicity to aphids than both PSO and thiamethoxam (positive control). This study emphasized the potential of PSO as a natural plant-derived insecticide in controlling cowpea aphids and also provided a novel approach for the value-added utilization of pomelo seed.